On the minimal speed of traveling waves for a non-local delayed reaction-diffusion equation - Aguerrea, M.; Valenzuela, G. (Нелінійні коливання, 2010)
In this note, we give constructive upper and lower bounds for the minimal speed of propagation of traveling waves for non-local delayed reaction-diffusion equation. Наведено конструктивнi верхня i нижня межi поширення пересуваючих хвиль для нелокального реакцiйно-дифузiйного рiвняння з запiзненням.